2016
DOI: 10.1002/ange.201609939
|View full text |Cite
|
Sign up to set email alerts
|

A Chiral Nitrogen Ligand for Enantioselective, Iridium‐Catalyzed Silylation of Aromatic C−H Bonds

Abstract: Iridium catalysts containing dative nitrogen ligands are highly active for the borylation and silylation of C-H bonds, but chiral analogs of these catalysts for enantioselective silylation reactions have not been developed. We report a new chiral pyridinyloxazoline ligand for enantioselective, intramolecular silylation of symmetrical diarylmethoxy diethylsilanes. Regioselective and enantioselective silylation of unsymmetrical substrates was also achieved in the presence of this newly developed system. Prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…The authors revealed that the system composed of iridium/ligand L 3 enabled highly enantioselective silylation of diarylmethanols to form cyclic silyl ethers in good to excellent yields with high enantioselectivity (Scheme 9(a)). [11] A proposed mechanism to consistent with the experimental results was presented in Scheme 9(b). A active Ir I À H species was generated in situ in the presence of precursor [Ir(cod)OMe] dimer, pyridinyloxazoline and monohydrosilane, followed by coordination and insertion of norbornene to form int II.…”
Section: Monohydrosilane-mediated C(sp 2 )à H Silylationsupporting
confidence: 61%
See 1 more Smart Citation
“…The authors revealed that the system composed of iridium/ligand L 3 enabled highly enantioselective silylation of diarylmethanols to form cyclic silyl ethers in good to excellent yields with high enantioselectivity (Scheme 9(a)). [11] A proposed mechanism to consistent with the experimental results was presented in Scheme 9(b). A active Ir I À H species was generated in situ in the presence of precursor [Ir(cod)OMe] dimer, pyridinyloxazoline and monohydrosilane, followed by coordination and insertion of norbornene to form int II.…”
Section: Monohydrosilane-mediated C(sp 2 )à H Silylationsupporting
confidence: 61%
“…In order to overcome the drawbacks of the above system, Hartwig and Shi group developed a new type of iridium/pyridinyloxazoline catalytic system, which overcame the drawbacks of previous work. The authors revealed that the system composed of iridium/ligand L 3 enabled highly enantioselective silylation of diarylmethanols to form cyclic silyl ethers in good to excellent yields with high enantioselectivity (Scheme 9(a)) [11] …”
Section: Monohydrosilane‐mediated C−h Silylationmentioning
confidence: 99%
“…Among all isotopes used to this end, deuterium plays a key role . Indeed, deuterium is not a radioactive nucleus like 3 H and 14 C, and it is less expensive than 13 C and 15 N. The versatility of deuterium-labeled molecules has been demonstrated in a wide range of applications, from proteomics, metabolomics, medical imaging, and drug discovery to tools for mechanistic investigations of bio-organic and organic reactions . In recent years, the demand for deuterium-labeled molecules has also increased due to the development of quantitative mass spectrometry analysis .…”
Section: Introductionmentioning
confidence: 99%
“…To develop a catalyst for the site-selective and enantioselective silylation, 11d23 of unactivated C(sp 3 )-H bonds of aliphatic amines, iridium complexes of a variety of chiral N,N -ligands were investigated as catalysts for the silylation of amine 2a (Table 4). An initial survey with chiral, nitrogen-based ligands that are commonly used in asymmetric catalysis, such as bis(oxazoline) ligands (e.g., L7 , entry 1) and pyridyl oxazoline ligands (e.g., L8 , entry 2) that formed highly enantioselective catalysts in our prior silylation of both C(sp 2 )-H and C(sp 3 )-H bonds, 23e23f showed that the reactivity and enantioselectivity of catalysts formed from these common classes of chiral N,N -based structures were low.…”
Section: Resultsmentioning
confidence: 99%